2021
DOI: 10.3390/fermentation7030182
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Erinacine A Production by Hericium erinaceus Using Solid-State Cultivation

Abstract: Hericium erinaceus (HE) is a large edible medicinal fungus. Erinacine A (ErA) is a secondary metabolite presented in the mycelia of HE, with pharmacological effects as a nerve growth factor on the central nervous system. In this study, solid-state cultivation of HE was carried out in Petri dishes and glass jars for the production of mycelial biomass and ErA. The potato dextrose agar (PDA) had the highest mycelial biomass at an optimal temperature of 25 °C, but no ErA was found in the agar media. In glass jar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The low productivity of erinacine A has hindered its development and application as a dietary supplement. In the past, great efforts have been made to increase the productivity of erinacine A [ 8 , 21 , 42 , 43 ]. Using submerged cultivation, the highest content and yield of erinacine A were reported to be 14.44 mg/g and 225 mg/L, obtained by optimizing the culture medium composition [ 21 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The low productivity of erinacine A has hindered its development and application as a dietary supplement. In the past, great efforts have been made to increase the productivity of erinacine A [ 8 , 21 , 42 , 43 ]. Using submerged cultivation, the highest content and yield of erinacine A were reported to be 14.44 mg/g and 225 mg/L, obtained by optimizing the culture medium composition [ 21 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using submerged cultivation, the highest content and yield of erinacine A were reported to be 14.44 mg/g and 225 mg/L, obtained by optimizing the culture medium composition [ 21 , 43 ]. In addition, Cheng et al [ 8 ] reported that solid-state cultivation could significantly increase the content of erinacine A, reaching 165.36 mg/g. At present, there was no literature focusing on the comparison of erinacine A contents in different H. erinaceus germplasm resources, or screening the high-content strains or cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations